2016
DOI: 10.1590/s1984-82502016000300015
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of topical herbal gel for the treatment of arthritis in animal model

Abstract: The objective of the study is to formulate and evaluate a topical herbal gel containing Cardiospermum halicacabum and Vitex negundo leaf extracts for their anti-arthritic activity in rats. Twelve herbal gel formulations were prepared using 1.5% of gelling agents carbopol 934 (F1-F6) and carbopol 940 (F6-F12) and they were evaluated for physical appearance, net content, viscosity, extrudability, pH, spreadability, in vitro diffusion profile and primary skin irritation tests. The stability study for the topical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 19 publications
2
93
1
Order By: Relevance
“…Where S = Spreadability in g cm s À1 ; M = Mass of gel placed between the two slides; L = Length of slide; t = Time taken by the upper slide to detach [39].…”
Section: Spreadabilitymentioning
confidence: 99%
“…Where S = Spreadability in g cm s À1 ; M = Mass of gel placed between the two slides; L = Length of slide; t = Time taken by the upper slide to detach [39].…”
Section: Spreadabilitymentioning
confidence: 99%
“…Where, M is the weight tied to upper slides (20 g), L is the length of the glass slide (7.5 cm) and T is the time taken in sec. 15…”
Section: …………………………(3)mentioning
confidence: 99%
“…Rate of release suggested that the drier the impregnation with thick film shows extended period of activity against mosquito. By addition of carbopol act as thickener as well as gelling matrix which enhance the activity of neem microemulsion (Aiyalu et al, 2016).…”
Section: Release Of Active Ingredientmentioning
confidence: 99%